Perceptions of Occupational Therapy Educators about the Educational Preparation of Occupational Therapists for Designation as Qualified Mental Health Professionals. Issue 2 (3rd April 2023) - Nissen, Ranelle M.; Ikiugu, Moses N.; Barash, Brenna; Kathol, MaKenzie; Oorlog, Ariana
Abstract: This study investigated educators' perspectives on whether occupational therapists were educationally prepared for designation as Qualified Mental Health Professionals (QMHPs) using a cross-sectional survey design followed by interviews to gather qualitative data. Fifty-two educators responded to an electronic survey questionnaire. Six of the 52 participants volunteered for follow-up interviews. Most educators (64.58%) thought that occupational therapists were prepared for designation as QMHPs ( p =.04). Interview data indicated that educational programs prepared students for psychosocial practice using various content delivery methods. Occupational therapists need to advocate for recognition as significant contributors to the treatment of people with mental health challenges.